2021
DOI: 10.3138/cjhs.2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

Let’s talk about sexual health education: Youth perspectives on their learning experiences in Canada

Abstract: Education, and by extension, school-based sexual health education for youth, falls under provincial and territorial jurisdiction in Canada, creating a tapestry of educational experiences across the country. Previous research has found general support for provid ing sexual health education in schools as reported by teachers, parents, and college/university students. The current study further explores this topic through an examination of the perspectives and opinions of high-school aged youth. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…This research supports the importance of prioritizing comprehensive sexual health education that covers a wide range of topics that include educational content about accessing local services and resources as well as acknowledging and understanding both the positive and negative aspects of sexual activity and relationships. The results also highlight the importance of different sources of access to information for youth, social influences and safe learning environments in the context of sex education [58].…”
Section: Discussionmentioning
confidence: 81%
“…This research supports the importance of prioritizing comprehensive sexual health education that covers a wide range of topics that include educational content about accessing local services and resources as well as acknowledging and understanding both the positive and negative aspects of sexual activity and relationships. The results also highlight the importance of different sources of access to information for youth, social influences and safe learning environments in the context of sex education [58].…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, some students may feel embarrassed or uncomfortable discussing sexual topics in a classroom setting. Overall, perceptions on this topic can be diverse (Laverty, Noble, Pucci & MacLean, 2021). In countries where sex education is a part of the curriculum and is taught comprehensively and age-appropriate, students may have a more positive perception of the initiative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, some students may feel embarrassed or uncomfortable discussing sexual topics in the classroom, and regardless of the country or cultural context. They may feel it is private and should not be discussed in a public setting like a school (Laverty, Noble, Pucci & MacLean, 2021). Studies have shown that students in Pakistan generally believe that sex education should be taught in schools, but they also express concerns about the quality and content of the education they receive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, school remains an essential source of reliable information for adolescents. [3][4][5] SH education is included in almost every secondary school curriculum, and it plays an important role in enhancing adolescent health and well-being. 3,6,7 School-based SH education offers age-appropriate and up-to-date knowledge, as well as the skills required to develop healthy relationships during adolescence and later on in adulthood.…”
mentioning
confidence: 99%
“…[3][4][5] SH education is included in almost every secondary school curriculum, and it plays an important role in enhancing adolescent health and well-being. 3,6,7 School-based SH education offers age-appropriate and up-to-date knowledge, as well as the skills required to develop healthy relationships during adolescence and later on in adulthood. 3 The main goal is to develop adolescents' knowledges, behaviors, and attitudes towards SH and ensure the appropriate level of knowledge and skills to improve it.…”
mentioning
confidence: 99%